Good Apples, Bad Apples: Sorting Among Chinese Companies Traded in the U.S - Ang, James S. (Journal of business ethics, 2016)
Committing financial fraud is a serious breach of business ethics. However, there are few large scale studies of financial fraud, which involve ethical considerations. In this study, we investigate the pervasive financial scandals, which by the end of 2012 involved more than a third of the US-listed Chinese companies. Based on a sample of 262 US-listed Chinese companies, we analyze factors that differentiate between firms that commit financial fraud and those that do not. We find that firms more predisposed to unethical behavior, due to their low regional social trust in the home country and low respect for regulations and laws as proxied by political connections, are more likely to commit accounting and financial fraud. They take advantage of low hurdles for listing via reverse mergers and avoid third-party monitoring through poor governance and auditors. Finally, we find evidence, after these scandals, of non-fraudulent firms differentiating themselves from the fraudulent firms by sending costly signals such as insiders purchasing shares, increasing dividends, and going private.